Overview of distinct N6-Methyladenosine profiles of messenger RNA in osteoarthritis - Yu, Yang; Lu, Shitao; Li, Yu; Xu, Jianzhong (Frontiers in Genetics, 2023)
Although N6-methyladenosine (m6A) modification is closely associated with the pathogenesis of osteoarthritis (OA), the mRNA profile of m6A modification in OA remains unknown. Therefore, our study aimed to identify common m6A features and novel m6A-related therapeutic targets in OA. In the present study, we identified 3962 differentially methylated genes (DMGs) and 2048 differentially expressed genes (DEGs) using methylated RNA immunoprecipitation next-generation sequencing (MeRIP-seq) and RNA-sequencing. A co-expression analysis of DMGs and DEGs showed that the expression of 805 genes was significantly affected by m6A methylation. Specifically, we obtained 28 hypermethylated and upregulated genes, 657 hypermethylated and downregulated genes, 102 hypomethylated and upregulated genes, and 18 hypomethylated and downregulated genes. The differential gene expression analysis based on GSE114007 revealed 2770 DEGs. The Weighted Gene Co-expression Network Analysis (WGCNA) based on GSE114007 identified 134 OA-related genes. By taking the intersection of these results, ten novel aberrantly expressed, m6A-modified and OA-related key genes were identified, including SKP2, SULF1, TNC, ZFP36, CEBPB, BHLHE41, SOX9, VEGFA, MKNK2 and TUBB4B. The present study may provide valuable insight into identifying m6A-related pharmacological targets in OA.